Prevalence of tuberculosis (TB) patients diagnosed in Sabah / Ayu Jonathan Seribu - Jonathan Seribu, Ayu (2014)
The aim of the present study was to determine the prevalence TB disease in Queen Elizabeth Hospital. This study employs a quantitative approach to data collection and analysis. The data collections were obtained from Jabatan Kesihatan Negeri Sabah and the result were analyzed using the Graph Prism Version 6. The data were collected from year 2011 until 2013. From the result, the risk of male getting TB at the age of more than 45 years old is about 4.5000 times the risk of a female getting TB at the same age. On the other hand for lesser than 45 years old were 0.6111 lesser than female. This showed those males were more affected with TB at the age more than 45 years. From the result, in age less than 45 year, the female are more death than male patients. Then, in age more than 45 year, the male are more death than female patient. It is based on the data from year 2011. In conclusion, the most important and effective way to prevent TB spreading in this country is to diagnose people with the disease as soon as possible and make sure they have a full course of correct treatment.